LATE PALEOZOIC – MESOZOIC TECTONIC EVOLUTION AND PROSPECTS OF HYDROCARBON EXPLORATION IN THE ALAKOL SEDIMENTARY BASIN (KAZAKHSTAN) - V. V. Korobkin; A. Ye. Chaklikov; A. A. Ismailov; Zh. S. Tulemissova (Геодинамика и тектонофизика)
Based on the analysis of stratigraphic, lithofacies, and geological and geophysical data, consideration is being given to the main stages in the formation of the basement and cover structures of the Alakol sedimentary basin. For this region, there was developed the substantiation of a scheme of tectonic zoning and there were proposed structural characteristics of faults and lithofacies features of the section. Evidence was found of a complex, multi-stage tectonic evolution. There were discovered potentially promising stratigraphic oil and gas complexes of the Late Paleozoic and Mesozoic. The deep-seated structure of the region is illustrated by a geological and geophysical section, spatially coincident with the "Turkestan" seismic profile. Based on the lithological and paleogeographic reconstructions, there were identified four major tectonic boundaries: Cambrian-Ordovician, Devonian-Carboniferous, Permian-Early Triassic, and Middle Triassic-Cretaceous. The correlation of the stratigraphic range of the hydrocarbon potential of the Alakol basin has been carried out. The criteria for forecasting hydrocarbon accumulations were substantiated.